THE SUSTAINABILITY REPORTING WITHIN THE ASEAN COUNTRIES; A BIBLIOMETRIC ANALYSIS REVIEW - Alfian Sayuti; Dedi Aprianto (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2023)
Sustainability reporting is  one of the company’s efforts to present non-financial information to stakeholders. It is hoped that this will increase the company’s transparency in all its activities related to the environment, social and economy. This study used a bibliometric analysis related to the previous studies related to the issue of sustainability reports. The current study was conducted by using data from the Scopus sources. The keyword used is sustainability reporting with a total data of 428 documents. The current study was carried out only for the ASEAN countries. The research identified several things including research contributions by countries, journals, topics, keywords, authorships, and affiliations. The finding shows that the ASEAN countries dominating the so-called studies related to the sustainability reporting is Malaysia and Indonesia. The mostly-used keywords are sustainability and sustainability reporting. This study also presents the data on journal affiliations and publishers who contributed to this study. The results have limitations including data sources and supporting software used. Sources of data only come from articles accredited by Scopus, then the data obtained is processed using only 1 software. The novelty of this research is to analyze the sustainability report issues by using a Bibliometric model in the ASEAN countries. It is expectedly used to provide more insight towards researchers and academia interested in discussing under sustainability reporting issues.